2019
DOI: 10.1038/s41598-019-44020-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stabilization of Viral Vaccines in Low-Cost Sugar Films

Abstract: Most currently available vaccines, particularly live vaccines, require the cold chain, as vaccine efficacy can be significantly hampered if they are not stored in a temperature range of 2–8 °C at all times. This necessity places a tremendous financial and logistical burden on vaccination programs, particularly in the developing world. The development of thermally stable vaccines can greatly alleviate this problem and, in turn, increase vaccine accessibility worldwide. In this paper, we detail a simple and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Currently, the development of thermostable vaccinesare yet unmet with little success in which thermal stability was observed (only for a few months at best and that too in few cases) (Leung et al 2019 ; Chu et al 2016 ; Mistilis et al 2017 ; Hassett et al 2013 ; Hassett et al 2015 ; Chen et al 2010 ; Ohtake et al 2010 ; Ohtake et al 2011 ; Lovalenti et al 2016 ). Thin-film coating was able to keep the adenovirus stable atambient temperature for 3 years ( Bajrovic et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the development of thermostable vaccinesare yet unmet with little success in which thermal stability was observed (only for a few months at best and that too in few cases) (Leung et al 2019 ; Chu et al 2016 ; Mistilis et al 2017 ; Hassett et al 2013 ; Hassett et al 2015 ; Chen et al 2010 ; Ohtake et al 2010 ; Ohtake et al 2011 ; Lovalenti et al 2016 ). Thin-film coating was able to keep the adenovirus stable atambient temperature for 3 years ( Bajrovic et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the addition of anionic nanogold particles and polyethene glycol improve the thermal stability of some of the vaccines significantly ( Pelliccia et al 2016 ) . Recently, the coating of bacterial cells or viral particles in a thin film of sugar gave promising results (Leung et al 2019 ; Bajrovic et al 2020 ). All the above-highlighted approaches used the addition of one or more chemicals in vaccine preparation which necessitates additional safety tests and other regulatory procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines are commonly stabilized by spray or freeze-drying in the presence of stabilizing protectors, such as carbohydrates 26 , 51 . Recently, stabilization of herpes simplex virus 2 and influenza A virus vaccines was achieved by simple evaporative drying (also known as desorption) in the presence of carbohydrates 52 . Unfortunately, desorption is a diffusion-limited process that is difficult to scale up for industrial purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Saboo et al reported successful spray drying of HPV VLPs into a dry powder, although this was only possible using a multi-component excipient system due to stresses exhibited during the process [ 22 ]. The research paradigm is shifting towards eliminating the cold chain altogether, with innovations in vaccine formulations and storage technology whereby the vaccine material is maintained to the highest integrity with exposure to the least amount of stress [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%